Pemanfaatan Daun Cengkeh (Syzygium aromaticum L.) Dalam Proses Pembuatan Virgin Coconut Oil (VCO) - Mangesa, Rosita; Irsan, Irsan (Biosel Biology Science and Education, 2020)
The clove leaves are part of the clove plant which rarely used, and if you look at them, the clove leaves have active compounds that can be functioned as antibacterials. Meanwhile, Virgin Coconut Oil or called VCO, is processed from coconut milk as the essential ingredient, and if it is not processed correctly, VCO will usually have a short shelf life or can be damaged quickly. This study aims to determine the quality of VCO by adding clove leaves in its processing. Based on the results of the study, it can be seen that the quality of VCO with the addition of clove leaves for the indicator of water content and the free fatty acid number is not following the Indonesian National Standard (SNI). In contrast, the indicator for the VCO peroxide number with a mixture of clove leaves has good quality according to the SNI standard. Based on the results of the study, it can be seen that the quality of VCO with the addition of 100 grams of clove leaves for indicators of water content and fatty acid numbers, namely 2.9% and 0.69%, is high or above the SNI standard limit. In comparison, the quality of VCO with the addition of 100 grams of clove leaves with indicators a peroxide value of 0.7 mg ek/ kg or less than 2 mg ek/kg has good quality based on Indonesian National Standard. Keywords: Quality, VCO